Investigation of Factors Affecting The Silicone Rubber Insulator And Nano dielectric Strength In High Voltage Power Transmission System - Srivastava, Vinit (My University, 2019)
In case of overhead transmission line insulator, five cases have been investigated from the electric field and polarization density distribution point of view. All cases focus at triple point junction of the water drop by comparing dry air to humid, by increasing the volume, by increasing the contact angle, by increasing the permittivity of pollution layer and by the presence of pollution particle. This study shows the simulation of the water drop at the 90degree contact angle on clean silicon rubber insulator under high voltage stress in 2D space dimension is shown, by using the finite element method based software. The simulation results provide deep insights about relation on local electric field intensification with environmental changing parameters. Where in case of nano composite, as the permittivity of the nanocomposite increases, comparison to ellipsoid water void, by increasing the permittivity of the base material and nano filler enhances the nano dielectric strength and by decreasing interparticle distance. Nano interface is considered as the cause for better insulation strength, but as its understanding is largely unknown. The simulation results show many aspects to enhance the dielectric strength from exploring interface. At last, a new approach to configure two particles has been investigated which results in finding the best configuration for better insulation. Finally, the practical importance of this work is that it can be used to understand nano interface in nanodielectrics and future investigators can use it as a guide to choose material for their next experiment in order to obtain better insulation.
Keywords: Triple Point Junction; Silicone Rubber; Polarisation Density; Finite Element Method; contact angle; Nono Composites